Taxonomic notes on Alpinia brevis and A. bambusifolia (Zingiberaceae) - Yan, Jiawei; Chen, Yousheng; Liu, Hua; Yi, Sirong; Chen, Juan (Phytotaxa, 2024)
The identities and nomenclature histories of two endemic gingers from China, viz. Alpinia brevis and A. bambusifolia, are reviewed. Alpinia brevis was previously thought to be a widespread species, distributed in Hainan, Guangxi and Yunnan, while A. bambusifolia was known to be endemic to Guangxi. Nevertheless, the results in this study suggest that the collections from Guangxi and Yunnan were misidentified as A. brevis, those of which from Guangxi should belong to A. jianganfeng or Globba aff. racemosa, while those from Yunnan should belong to A. bambusifolia. The treatment that A. nanchuanensis is a synonym of A. bambusifolia is supported by our studies. After this revision, A. brevis is restricted to Hainan, while A. bambusifolia occurs in Chongqing, Guangxi, Guizhou and Yunnan, China. Lectotype is designated for A. nanchuanensis here.